Individual Factors Influence the National Competency Examination Failure in Midwifery Students - Sari, Ade Zayu Cempaka; Kartasasmita, Arief Sjamsulaksana; Herman, Herry (Universitas Gadjah Mada, 2024)
Background: Incompetent and inadequate human health resources lead to a declining quality of health services. A quality assurance education system is needed to provide good quality training for healthcare workers. National competence tests are part of the guaranteed measurement of quality education. This study aimed to explore individual student factors that influence the failure to pass the competence test on the nursing competency test.Methods: This research is qualitative research with a phenomenological approach. Data collection using snowball sampling techniques by conducting in-depth interviews in an unstructured manner. The subject of the research was 7 alumni of the DIII Study Program Poltekkes Kemenkes Bengkulu who never passed the competence test. The analysis used is thematic analysis.Results: Individual factors influencing the failure to pass the competence test are low learning interest, low motivation, lack of self-confidence, anxiety, and inability to work on competence tests. This lack of self-confidence involves not understanding how to answer questions, not taking studying seriously, asking challenging questions, and not studying enough. Informants' lack of enthusiasm in studying was caused by them taking things too lightly, believing they would undoubtedly pass, there was a GPA point evaluation, they were lethargic, spent too much time on their cell phones, and were preoccupied with final assignment reports. The majority of respondents stated that they did not feel motivated to study to pass the competency test. Anxiety is frequently felt during tests since students do not comprehend the strategies for answering questions and the time is too short. Aside from that, they are not meticulous in answering the questions because they are in a rush.Conclusion: There are 5 individual factors influencing the failure of students to pass the competence test. Knowing the individual factors that can affect the lack of competence test, the educational institution can optimize the student's self factor following the competency test.